2014
DOI: 10.1136/bjophthalmol-2014-305915
|View full text |Cite
|
Sign up to set email alerts
|

Topical brinzolamide (Azopt) versus placebo in the treatment of infantile nystagmus syndrome (INS)

Abstract: NCT01312402.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 25 publications
0
7
0
2
Order By: Relevance
“…These medicinal products produce less side effects compared to the first-generation drugs 74,75. Brinzolamide is reabsorbed from the blood to a small extent, which results in low systemic blood concentrations and only few side effects could be expected 72,75. Nevertheless, nausea and interference in taste may occur.…”
Section: Drug Classesmentioning
confidence: 99%
“…These medicinal products produce less side effects compared to the first-generation drugs 74,75. Brinzolamide is reabsorbed from the blood to a small extent, which results in low systemic blood concentrations and only few side effects could be expected 72,75. Nevertheless, nausea and interference in taste may occur.…”
Section: Drug Classesmentioning
confidence: 99%
“…Only 22% of the included studies reported visual acuity and these were mostly for nystagmus or orbital abnormalities. “Binocular visual acuity” was specifically additionally indicated in two of nystagmus studies [85, 126].…”
Section: Resultsmentioning
confidence: 99%
“…To date, RCT evidence for treatment of INS is scarce; only four RCTs have been undertaken in this field. These have explored auditory biofeedback (Evans et al, 1998), pharmacological treatments (McLean et al, 2007;Hertle et al, 2015) and contact lenses (Jayaramachandran et al, 2014). Supplementary table 6 lists the main similarities and differences between the randomized CL trial (Jayaramachandran et al, 2014) and our study.…”
Section: Discussionmentioning
confidence: 99%